The Effectiveness of Rondo Game Variations in Improving the Passing and Controlling Skills of U-13 Soccer Athletes - Hafiz Zikrillah Hafizzra; Muhamad Tafaqur; Ridha Mustaqim; Mulyana Mulyana (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
The problem faced is the low ability of passing and controlling the ball in SSB Perbi FC Bandung Regency athletes. The purpose of this study is to provide a solution to the problem by using rondo games training as a method to improve the ability of passing and controlling the ball. The approach used in this research is an experiment with a one group pre-test post-test design. The population of this study were soccer athletes SSB Perbi FC Kab. Bandung, with a sample size of 10 people selected through purposive sampling. The data collection technique is done through measuring the ability of passing and controlling the ball before and after the rondo variation training. The data analysis technique used is descriptive analysis with average calculations and t tests to determine differences before and after treatment. The results showed that rondo variation training can significantly improve the ability of passing and controlling the ball. Based on these results, it can be concluded that intense rondo variation training can provide a significant improvement in the passing and controlling skills of soccer athletes SSB Perbi FC Bandung Regency. The novelty of this research lies in the application of variations of rondo games as a solution to improve the ability of basic soccer techniques in young age groups